It eill work when : replace :: Eq a => a -> a -> [a] -> [a] will be. How can I convert az a to an [a] in my code ?
replace :: Eq a => a -> [a] -> [a] -> [a]
replace _ _ [] = []
replace a x (y:ys)
| a == y = x : replace a x ys
| otherwise = y : replace a x ys
Example:
replace '?' "a" "" == ""
replace 'a' "e" "alma" == "elme"
replace 'a' "e" "nincsbenne" == "nincsbenne"
CodePudding user response:
You are using wrong operator for the first guard (a == y
) - :
is used to prepend a head element to a list but x
is a list not a single element, so you need to use
which concatenates two lists (x
and one returned by recursive call):
replace :: Eq a => a -> [a] -> [a] -> [a]
replace _ _ [] = []
replace a x (y:ys)
| a == y = x replace a x ys -- instead of :
| otherwise = y : replace a x ys
Related - Haskell (:) and ( ) differences